Multiple Solutions for a Fractional $p$-Laplacian Equation with Concave Nonlinearities (Journal of Partial Differential Equations, 2020)
We investigate a fractional $p$-Laplacian equation with right-hand-side nonlinearity which exhibits $(p-1)$-sublinear term of the form $λ |u|^{q-2},\, q
Keywords: Fractional $p$-Laplacian problems; Morse theory; concave nonlinearities; existence and multiplicity of solutions.